An explorative study on Features of microinsurance schemes conplementing poverty alleviation role of microfinance and microinsurance service delivery mechanisms selected microfinance institutes (MFIs) in Bangladesh - Siddiky, Shakera (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2007.